COMPARATIVE CRYSTAL CHEMISTRY OF GEMINITE CU[ASO3OH]H2O AND THE MINERALS ASSOCIATED WITH IT - Principe M.; Pushcharovskiy D.Yu.; Sarp M.; Ferraris G. (My University, 1996)
The structure of geminite was studied and compared with that of arsenates of Zn, Co, Mn, and Ca which are chemically close to it. The structural investigation was carried out on a single crystal of geminite from Salcine in France, where it was discovered in association with arsenopyrite, chalcopyrite, tellurium, pushcharovskite and other minerals. The study was based on chemical microprobe analysis and single crystal diffractometry.